2012
DOI: 10.1177/147323001204000242
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Differentiation of Osteocytes and Adipocytes from Human Placenta-Derived Cells

Abstract: Placenta-derived adherent cells can differentiate into either osteocytes or adipocytes in vitro. The human placenta may provide an alternative source of mesenchymal stem cells for basic research and clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Furthermore, according to our observations, the untreated SLCs expressed neural markers and could differentiate into neural lineage after a shorter induction period as compared with NTERA-2 cells. To investigate mesodermal differentiation of SCLs, an osteogenic medium, containing dexamethasone, ascorbate-2-phosphate and b-glycerol phosphate, was used based on several reports and our previous experience (Covas et al 2003;Ahmadian Kia et al 2011;Sun and Ji 2012). Differentiation of SLCs toward osteocytes was confirmed by their mineralized matrix stained with Alizarin Red S. RT-PCR studies also indicated the expression of Ocn and Opn in differentiated SLCs, quite similar to induced rMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, according to our observations, the untreated SLCs expressed neural markers and could differentiate into neural lineage after a shorter induction period as compared with NTERA-2 cells. To investigate mesodermal differentiation of SCLs, an osteogenic medium, containing dexamethasone, ascorbate-2-phosphate and b-glycerol phosphate, was used based on several reports and our previous experience (Covas et al 2003;Ahmadian Kia et al 2011;Sun and Ji 2012). Differentiation of SLCs toward osteocytes was confirmed by their mineralized matrix stained with Alizarin Red S. RT-PCR studies also indicated the expression of Ocn and Opn in differentiated SLCs, quite similar to induced rMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies expected the hPSCs to serve as building blocks of damaged tissues [ 182 , 187 , 188 , 189 , 190 , 191 , 192 , 193 ], but they seem to have limited differentiation potential [ 120 , 126 , 137 , 148 , 181 , 184 , 194 , 195 , 196 ]. The activity of hPSCs in allogeneic and xenogeneic administration seems to derive from their rich secretome, activated in response to a wide range of stress signals [ 114 , 130 , 180 , 197 , 198 , 199 , 200 , 201 , 202 , 203 ].…”
Section: Application Of Hpscs From Mature Placentae For Tissue Regeneration and Immune Modulationmentioning
confidence: 99%
“…Numerous studies have demonstrated the differential potential and multilineage capacity of the placental derived stem cells through in vitro characterization and differentiation experiments (Sabapathy et al, 2012;Sun and ji, 2012;Susman et al, 2010;Chien et al, 2006). Recently, it has been reported that the placental derived stem cells differentiate into osteocytes, chondrocytes, adipocytes, hepatocytes and cardiomyocytes under specific culture conditions (Sabapathy et al, 2012;Sun and ji, 2012;Susman et al, 2010;Chien et al, 2006;Okamoto et al, 2007).We have selected differentiation pathways which are more important for the future program of stem cell transplantation at our institute -one is the use of cardiomyocytes in myocardial infarction and the another one is the use of osteocytes for bone disorders and bone tissue engineering (Sharma et al, 2013 (In press); Gupta et al, 2013 (In press); Potdar and S Kumar. 2013;Potdar and Prasanan, 2013).…”
Section: Expression Of Cardiomyocytes and Osteocytes Genes In Fetal Amentioning
confidence: 99%
“…All these markers are indications of specific phenotypes of stem cells. Differential potential of placental stem cells in to cardiomyocytes and osteocytes can be confirmed by expression of cardiac β heavy chain myosin, cardiac troponin and cardiac actin and ALP and OCN markers respectively (Sabapathy et al, 2012;Sun and ji, 2012;Susman et al, 2010;Chien et al, 2006;Okamoto et al, 2007). Few studies have shown an importance of some of the genes such as CD73, CD45, CD100, Vimentin and Ki67 in maintenance of human pregnancy.…”
Section: Introductionmentioning
confidence: 97%